First Complete Genome of Reticuloendotheliosis Virus in a Mallard Duck from Brazil: Phylogenetic Insights and Evolutionary Analysis - Ruy D. Chacón; Claudete S. Astolfi-Ferreira; Stefhany Valdeiglesias Ichillumpa; Henrique Lage Hagemann; Maristela Furlan Rocha; Larissa Fernandes Magalhães; Tânia Freitas Raso; Antonio J. Piantino Ferreira (Pathogens)
Reticuloendotheliosis virus (REV) is an oncogenic retrovirus that affects both commercial and free-ranging birds. To date, only two complete REV genome sequences have been identified in chickens from South America, with no records in other avian species. This study reports the first complete genome of REV detected in a mallard duck (Anas platyrhynchos domesticus) in South America. In 2021, a mallard duck in Brazil died from severe lymphoproliferative disease affecting multiple organs. Molecular detection and histopathological analysis confirmed REV as the causative agent. Using dideoxy sequencing and phylogenetic analysis, the virus was classified as subtype 3 (REV-3). The phylogenetic analysis identified three clades, each with a bootstrap value of 100, corresponding to the three REV subtypes. Furthermore, a comprehensive comparative genomic analysis revealed two distinct REV-3 subclusters—‘East’ (38 strains) and ‘West’ (24 strains)—with notable geographical associations. Additionally, 27 genomes in chimeric states with fowlpox virus (FWPV) were distributed across the phylogenetic tree, emphasizing the critical role of FWPV in the dissemination of REV. Selective pressure analysis revealed evidence of positive selection acting on several codons within the gag, pol, and env genes, particularly in domains such as matrix, p18, reverse transcriptase/ribonuclease H, and surface. These findings provide valuable insights into REV evolution and underscore the importance of genomic surveillance for detecting REV circulation in diverse hosts.